Changes in the microbiota in different intestinal segments of mice with sepsis - Peng, Yahui; Wei, Jieling; Jia, Xiaonan; Luan, Feiyu; Man, Mingyin; Ma, Xiaohui; Luo, Yinghao; Li, Yue; Li, Nana; Wang, Qian; Wang, Xibo; Zhou, Yang; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction The small intestine, as the main digestion and absorption site of the gastrointestinal tract, is often overlooked in studies, and the overall microbiota does not reflect the makeup of the microbiota in different segments of the intestine. Therefore, we aimed to exclude the influence of routine ICU treatment measures on sepsis patients and observed changes in the diversity and abundance of gut microbiota in different intestinal segments of septic mice. Methods The mice were randomly divided into the CLP6h group and the sham group. The contents of the colon and small intestine of the experimental group and the control group were collected after 6 h. Results After CLP, the number and structure of the gut microbiota in the colon changed most obviously, among which Bacteroidetes had the most significant changes. Akkermansia, D.Firmicutes_bacterium_M10_2, Blautia, Bifidobacterium, Lactobacillus, Candidatus_Arthromitus, and Muribaculaceae were changed in the colon. Lactobacillus, Bifidobacterium, Akkermansia, Blautia, Candidatus_Arthromitus, and Lachnospiraceae_NK4A136_group were changed in the small intestine. Discussion Our experiment found that there were different numbers of unique and common gut microbiota in the small intestine and colon after sepsis, and the gut microbiota of the colon changed more drastically after sepsis than the small intestine. Thus, we should focus on protective gut microbiota and mucin-degrading microbes. We hope that these results will provide help for sepsis treatment in the future.